Noninvasive fetal genotyping in pregnancies at risk for PKU using a comprehensive quantitative cSMART assay for PAH gene mutations: a clinical feasibility study. (16th August 2019) - Lv, W; Li, Z; Wei, X; Zhu, H; Teng, Y; Zhou, M; Gong, Y; Cram, DS; Liang, D; Han, L; Wu, L
Abstract : Objective: To assess the diagnostic performance of a novel circulating single molecule amplification and re‐sequencing technology (cSMART) method for noninvasive prenatal testing (NIPT) of Phenylketonuria (PKU). Design: Blinded NIPT analysis of pregnancies at high risk for PKU. Setting: Shanghai Xinhua Hospital and Hunan Jiahui Genetics Hospital, China. Population: Couples ( n  = 33) with a child diagnosed with PKU. Methods: Trio testing for pathogenic PAH mutations was performed by Sanger sequencing. In second pregnancies, invasive prenatal diagnosis (IPD) was used to determine fetal genotypes. NIPT was performed using a PAH gene‐specific cSMART assay. Based on the plasma DNA mutation ratio relative to the fetal DNA fraction, fetal genotypes were assigned using a maximum‐likelihood algorithm. Main outcome measures: Concordance of fetal genotyping results between IPD and NIPT, and the sensitivity and specificity of the NIPT assay. Results: Compared with gold standard IPD results, 32 of 33 fetuses (96.97%) were accurately genotyped by NIPT. The sensitivity and specificity of the NIPT assay was 100.00% (95% CI 59.04–100.00%) and 96.15% (95% CI 80.36–99.90%), respectively. Conclusions: The novel cSMART assay demonstrated high accuracy for correctly calling fetal genotypes. We propose that this test has useful clinical utility for the rapid screening of high‐risk and low‐risk pregnancies with a known history of PKU on one or both sides of the family. Tweetable abstract: NIPT of couples at high risk for PKU using a full‐coverage cSMART PAH gene test.